The culture of women in tech : an unsuitable job for a woman - Hardey, Mariann (Emerald points., 2019)
This book offers a critical analysis of the contemporary and global tech culture and exposes the gender bias of masculine tech ideology and stereotypes. Is the place of 'women in tech' immovable from masculine leadership practices? And what are the cultural, social, personal and economic consequences of gender as a point of difference in the context of work in the tech sector? Mariann Hardey examines the rise of entrepreneurial work and leadership, the contemporary urban setting of global tech work, and specifically women's place in tech clusters. The book engages with attempts by women to establish and then sustain their professional status and long-term careers, despite predatory social media trolling and inappropriate sexualized behaviour. Based on a series of commentaries from research undertaken by the author about workers located within 'tech cities' in the UK, USA and East Asia regions, the work exposes the serious problem of women's position in the industry. While this study continues to be critical of the conceits of masculine tech ideology, prejudices and stereotypes, the work contributes to recent calls to help find solutions and ways forward.